2015
DOI: 10.1080/15592294.2014.998536
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation abnormalities in congenital heart disease

Abstract: Congenital heart defects represent the most common malformation at birth, occurring also in »50% of individuals with Down syndrome. Congenital heart defects are thought to have multifactorial etiology, but the main causes are largely unknown. We have explored the global methylation profile of fetal heart DNA in comparison to blood DNA from control subjects: an absolute correlation with the type of tissue was detected. Pathway analysis revealed a significant enrichment of differential methylation at genes relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 48 publications
1
78
0
Order By: Relevance
“…A case-control study from Spain reported absence of maternal folic acid supplementation was more frequent in DS with atrioventricular septal defects (OR = 1.69, 95% CI = 1.08 -2.63) or atrial septal defects (OR = 1.69, 95% CI= 1.11 -2.58) compared to DS without CHD (18). Thus, maternal supplementation with folic acid is likely to be associated with reduced risk of CHD in DS.…”
Section: Resultsmentioning
confidence: 99%
“…A case-control study from Spain reported absence of maternal folic acid supplementation was more frequent in DS with atrioventricular septal defects (OR = 1.69, 95% CI = 1.08 -2.63) or atrial septal defects (OR = 1.69, 95% CI= 1.11 -2.58) compared to DS without CHD (18). Thus, maternal supplementation with folic acid is likely to be associated with reduced risk of CHD in DS.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, DNA methylation is closely associated with gene expression regulation, and it is well-known that aberrant DNA methylation may contribute to the occurrence of various diseases such as heart disease [20], Alzheimer's disease [21] and cancer [22,23]. The development of NGS technology has accelerated genetics and epigenetics research, concomitantly advancing the development of diverse DNA methylation analysis technologies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, population and experimental studies have provided evidence to support the role of folate metabolism in healthy development, through regulation of methylation modifications of the genome (Crott et al, 2008;Wang et al, 2010;Crider et al, 2012;Serra-Juhe et al, 2015). MTHFR genotypes are believed to alter folate metabolism in cells (Kim et al, 2010;Tsang et al, 2015) and subsequently modify methylation.…”
Section: Discussionmentioning
confidence: 99%